CUSTOMER VALUE, BEHAVIOR AND SATISFACTION: IMPACT OF THE COVID-19 PANDEMIC MATARAMAN VILLAGE CASE STUDY, PANGGUNGHARJO VILLAGE SOCIAL LAB YOGYAKARTA NAHDLATUL ULAMA UNIVERSITY - Budi Sutiono Pratama Nugraha; Nurul Salehawar (Universitas Wahid Hasyim Semarang, 2023)
Abstract This study aims to determine customer value, behaviour and satisfaction due to the impact of the Covid-19 pandemic, as well as the effect of customer value, behaviour and satisfaction on customer decisions. shopping at the Kampung Mataraman restaurant. The research method used is descriptive quantitative, with a sample of 103 respondents using simple random sampling, interview data collection and distribution of questionnaires. Findings: First , on the variable Customer value on the purchase decision has no partial positive effect on purchase decisions during the covid 19 pandemic. Second, the customer behaviour influence variable on purchasing decisions has a positive effect on purchasing decisions during the covid 19 pandemic. Third, the customer satisfaction variable on purchase decisions positive effect on purchase decisions during the Covid-19 pandemic. Fourth, the influence of X1, X2 and X3 simultaneously on purchase has a strong influence on the variable Customer Value , Customer Behaviour and Customer Satisfaction simultaneously on purchase. For the customer behaviour variable it has a positive effect on purchase decisions during the Covid-19 pandemic at Kampung Mataraman restaurant based on research results, this factor is a factor that continues to be taken into account and maintained because consumers always pay attention to values as a reference in making purchasing.Social, personal and psychological factors, these three factors must continue to be the concern of marketers in the age of the digital market and the changes in consumer behaviour that are so dynamic must continue to be of concern to marketers Key word : Customer Value, Behaviour, Satification, Covid 19, Mataraman Village